A normative ethical analysis of Islamic unit-linked insurance using the Maqasid Shariah framework of Abu Zahrah - Kholis, Nur (Universitas Islam Indonesia, 2025)
IntroductionIslamic unit-linked insurance (IULI) products are widely offered in Indonesia as financial instruments that integrate Shariah-compliant protection and investment features. While these products formally adhere to legal Shariah contracts, growing concerns have emerged regarding their operational alignment with Islamic ethical principles, particularly justice. Previous studies have focused on the legal structure of Islamic insurance, but few have assessed whether their practices fulfill the higher objectives of Islamic law (maqasid shariah), especially from a normative ethical perspective.ObjectivesThis study aims to evaluate the operational practices of Islamic unit-linked insurance in Indonesia through the lens of maqasid shariah as conceptualized by Abu Zahrah. It seeks to determine whether the structural compliance of IULI contracts also translates into ethical and social justice in practice, particularly in cost transparency, fund management, and participant equity.MethodUsing a normative qualitative approach, this study analyzed policy documents, fatwas issued by Indonesia’s Shariah authority, and cost structures of four major Islamic insurance providers. The analysis applied Abu Zahrah’s three-dimensional maqasid framework—spiritual integrity, justice, and public welfare—to assess the alignment between contract theory and actual implementation. Contractual, regulatory, and ethical aspects were examined in light of Islamic jurisprudence.ResultsThe study found that while the IULI contracts were formally Shariah-compliant, operational practices exhibited major ethical inconsistencies. These include disproportionate acquisition costs, ambiguous fund classification, and vague contract disclosures. The clause allowing